2014
DOI: 10.1063/1.4885395
|View full text |Cite
|
Sign up to set email alerts
|

End-to-end and side-by-side assemblies of gold nanorods induced by dithiol poly(ethylene glycol)

Abstract: The assemblies of gold nanorods (Au NRs) exhibit unique properties distinct from the isolated Au NR. We report an effective and simple method for the end-to-end (E-E) and side-by-side (S-S) assemblies of Au NRs with a molecularly defined nanogap (1–2 nm) only in the presence of dithiol poly(ethylene glycol) (HS-PEG-SH). The assembled methods need neither the pH value adjustments nor the addition of other organic solvent. With increasing amount of dithiol molecules, assembled modes of Au NRs experience an inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…Bonding between the thiol moiety and Au is more prominent because of the strong Au−S covalent bond formation (∼209 kJ/mol or 84.5 k B T), 61,62 which has been widely used in NR functionalization. 15,36,42 Au-bonded cysteamine linkers can connect two adjacent Au NRs via hydrogen bonding (N−H•••N), as illustrated in Figure 1A. We found that depending on the linker concentration in solution, NRs assemble through two different attachment modes: (1) endto-end attachment (Figure 1B) at low (150 μM) and (2) sideto-side (Figure 1C) attachment at high (500 μM) cysteamine concentrations.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Bonding between the thiol moiety and Au is more prominent because of the strong Au−S covalent bond formation (∼209 kJ/mol or 84.5 k B T), 61,62 which has been widely used in NR functionalization. 15,36,42 Au-bonded cysteamine linkers can connect two adjacent Au NRs via hydrogen bonding (N−H•••N), as illustrated in Figure 1A. We found that depending on the linker concentration in solution, NRs assemble through two different attachment modes: (1) endto-end attachment (Figure 1B) at low (150 μM) and (2) sideto-side (Figure 1C) attachment at high (500 μM) cysteamine concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…At low linker concentrations, the CTA + ions that have less affinity for the {111} facets at the NR ends 63,64 are easily displaced by thiol. 42 This results in NRs with cysteamine-coated ends. The formation of hydrogen bonds between the cysteamine molecules of two NRs then leads to their end-to-end attachment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We speculate that these two assembly modes were closely related to the affinity of the Au-S binding and the repulsion between the cationic CTAB molecules on the side. 33 Crosslinker 1 has two functional groups, a thiol group and a 2-ureido-4(1H)-pyrimidinone moiety, and both can form bonds with Au. Bonding between the thiol moiety and Au is more favored because of the strong Au-S covalent bond formation.…”
mentioning
confidence: 99%